PEMANFAATAN EKSTRAK BIJI ALPUKAT (Persea americana Mill) UNTUK MENURUNKAN KANDUNGAN ASAM LEMAK BEBAS (ALB) DI DALAM MINYAK SAWIT MENTAH - Eka Nuryanto; Iput Pradiko; Zulfi Prima Sani Nasution (Pusat Penelitian Kelapa Sawit, 2016)
Mixing Crude Palm Oil (CPO) with high and lower Free Fatty Acid (FFA) is a technique to reduce FFA in CPO. Avocado Seeds Extract (ASE) was expected to reduce the FFA. This study was conducted to test the ability of ASE on reducing ALB in CPO. The variable in this study is ASE solution (0-50 ml). The whole treatment were conducted at same level of o temperatur 60 C, stirring speed (400 rpm) and reaction time (60 minutes). The research was employed non factorial Completely Randomized Design. Statistical analysis was performed using F Test along with Duncan Test. The results showed that addition of ASE can reduce FFA. The results of F Test showed that the addition of 25 ml ASE is the most effective for reduction ALB content (4.65 % to 0.22 %) in CPO.